Upaya Pentingnya Keabsahan Suatu Kontrak Elektronik yang Dilakukan Anak Dibawah Umur dalam Aplikasi Perdagangan Elektronik - Metta Valoka; Richard C. Adam (LPPM Universitas Ekasakti Padang, 2023)
To make an electronic contract, a condition is needed to fulfill the contract to be agreed upon and one of the subjective requirements is the ability of the parties in accordance with what is regulated in Article 1320 of the Civil Code. In this writing, it discusses minors who shop online which certainly does not meet the requirements for the validity of a contract. The problems that will be discussed in this journal, What are the consequences if the validity of electronic contracts carried out by minors conducting buying and selling transactions in electronic commerce applications and efforts to organize electronic systems to prevent violations of subjective requirements regarding the incompetence of minors who make electronic contracts in electronic commerce applications or E-commerce. The purpose of writing this journal is to understand more about the efforts and what to prevent so that minors do not shop online in the future. The type of research method that will be carried out is normative juridical. It can be concluded that before being carried out the consequences of electronic contracts carried out by minors can be canceled and bring other consequences and there are efforts that can be made to prevent minors from buying and selling transactions.